Biocatalytic Production of Amino Carbohydrates through Oxidoreductase and Transaminase Cascades. Issue 4 (29th January 2019) - Aumala, Ville; Mollerup, Filip; Jurak, Edita; Blume, Fabian; Karppi, Johanna; Koistinen, Antti E.; Schuiten, Eva; Voß, Moritz; Bornscheuer, Uwe; Deska, Jan; Master, Emma R.
Abstract: Plant‐derived carbohydrates are an abundant renewable resource. Transformation of carbohydrates into new products, including amine‐functionalized building blocks for biomaterials applications, can lower reliance on fossil resources. Herein, biocatalytic production routes to amino carbohydrates, including oligosaccharides, are demonstrated. In each case, two‐step biocatalysis was performed to functionalized ‐galactose‐containing carbohydrates by employing the galactose oxidase from Fusarium graminearum or a pyranose dehydrogenase from Agaricus bisporus followed by the ω‐transaminase from Chromobacterium violaceum ( Cvi ‐ω‐TA). Formation of 6‐amino‐6‐deoxy‐d ‐galactose, 2‐amino‐2‐deoxy‐d ‐galactose, and 2‐amino‐2‐deoxy‐6‐aldo‐d ‐galactose was confirmed by mass spectrometry. The activity of Cvi ‐ω‐TA was highest towards 6‐aldo‐d ‐galactose, for which the highest yield of 6‐amino‐6‐deoxy‐d ‐galactose (67 %) was achieved in reactions permitting simultaneous oxidation ofd ‐galactose and transamination of the resulting 6‐aldo‐d ‐galactose. Abstract : Two‐step biocatalysis : Fully biocatalytic cascades involving a carbohydrate oxidoreductase (galactose oxidase or pyranose dehydrogenase) and an ω‐transaminase are developed for the functionalization ofd ‐galactose‐containing carbohydrates to amino carbohydrates, and thus the production of amine‐functionalized building blocks for biomaterials applications is facilitated.